DETERMINATION OF POWER MILL SPENT ON THE CREATION OF THE LONGITUDINAL MOTION OF THE GRINDING LOAD - Romanovich, Alexey; Stepanovich, Bogdanov Vasiliy; Romanovich, Liudmila Gennadievna; Romanischin, Dmitry Viktorovich (Journal of Applied Engineering Science, 2015)
In this article, a method of grinding material stepwise realized in the roller press mill and a ball mill, equipped with energy-exchange units (LEU). It was found that when using a ball mill, equipped with LEU, depending on the angle of rotation of the drum periodically changes its load level of grinding media in the chambers, and in the zone of active influence of LEU is lifted and to give them the longitudinal-transverse movement, characterized by, created in traditional mills. The technique of determining the power consumed by the mill is further equipped with energy-exchange units consumed for longitudinal movement of the grinding bodies in the grinding of materials, previously ground to a roller press mill. Presented equation for its calculation. The influence on the additional power consumption of the length of the first chamber, the angle of energy-exchange devices and load factors cameras grinding bodies. Comparative results obtained by experiment and calculations.